Dependence on Base Width and Doping Concentration of Current Degradation in Gate-controlled Lateral PNP Bipolar Transistors Exposed to Reactor Neutrons and Gamma Rays. (September 2017) - Wang, Chenhui; Chen, Wei; Jin, Xiaoming; Liu, Yan; Yang, Shanchao
Abstract: Bipolar devices are widely used in the nuclear reactor control system, and the radiation effects on them are very important to reactor operation. The lateral PNP bipolar transistor is a radiation-sensitive structure in bipolar integrated devices. Its degradation under irradiation is the primary cause for functional failures of bipolar integrated devices. It is useful to understand the radiation response of the transistors to find better design strategies for radiation hardness. Three kinds of gate-controlled lateral PNP bipolar transistors (GCLPNPs) with different base widths and doping concentrations are specially designed to explore base current degradation induced by reactor neutrons and gamma rays. Dependence on base width and doping concentration of the degradation is analyzed in this work and the results are beneficial to radiation-hardening design of the lateral PNP bipolar transistor.